if a and b are roots of x 2 − 3 x + 1 = 0 then find the value of a 2 0 1 5 + b 2 0 1 5 a 2 0 1 4 + b 2 0 1 4 + a 2 0 1 6 + b 2 0 1 6 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes this is basically Newton's Sum. Well done again!
OOPP.. Never thought that way...
If a and b are the roots of the given quadratic equation
⟹ a 2 − 3 a + 1 = 0 and b 2 − 3 b + 1 = 0
⟹ a 2 + 1 = 3 a and b 2 + 1 = 3 b ............................... (1)
Now on rearranging the terms in the numerator the given expression is:
a 2 0 1 5 + b 2 0 1 5 a 2 0 1 6 + a 2 0 1 4 + b 2 0 1 6 + b 2 0 1 4
= a 2 0 1 5 + b 2 0 1 5 a 2 0 1 4 ( a 2 + 1 ) + b 2 0 1 4 ( b 2 + 1 )
= a 2 0 1 5 + b 2 0 1 5 a 2 0 1 4 . 3 a + b 2 0 1 4 . 3 b Using (1)
= ( a 2 0 1 5 + b 2 0 1 5 ) 3 ( a 2 0 1 5 + b 2 0 1 5 )
= 3
Let x n = a n + b n . According to the theory of Binet Forms, we have the recursive equation x n = 3 x n − 1 − x n − 2 , or, x n − 1 x n − 2 + x n = 3 . Applying this equation to n = 2 0 1 6 , we find the answer, 3 .
a + b = 3 a n d a b = 1 . ( a 2 0 1 5 + b 2 0 1 5 ) ∗ ( a + b ) = a 2 0 1 6 + b 2 0 1 6 + a b ∗ ( a 2 0 1 4 + b 2 0 1 4 ) ⟹ a 2 0 1 5 + b 2 0 1 5 = 3 a 2 0 1 6 + b 2 0 1 6 + 1 ∗ ( a 2 0 1 4 + b 2 0 1 4 ) ∴ f ( a , b ) = 3
Problem Loading...
Note Loading...
Set Loading...
Since a is a root we have : a 2 − 3 a + 1 = 0
Let's see what we get after multiplying both sides by a 2 0 1 4 . Indeed we get the following expression:
a 2 0 1 6 − 3 a 2 0 1 5 + a 2 0 1 4 = 0
Similarly we get :
b 2 0 1 6 − 3 b 2 0 1 5 + b 2 0 1 4 = 0
Adding both the above equations , we get :
a 2 0 1 4 + b 2 0 1 4 + a 2 0 1 6 + b 2 0 1 6 − 3 a 2 0 1 5 − 3 b 2 0 1 5 = 0 ⇒ a 2 0 1 4 + b 2 0 1 4 + a 2 0 1 6 + b 2 0 1 6 = 3 ( a 2 0 1 5 + b 2 0 1 5 ) ⇒ a 2 0 1 5 + b 2 0 1 5 a 2 0 1 4 + b 2 0 1 4 + a 2 0 1 6 + b 2 0 1 6 = 3